Code-Switching In Ritueli Daeli’s Youtube Playlist: A Content Analysis Of ‘Learning Englishfrom Zero’ Episodes 1–5 - Indana Zulva Wulandari; M. Ridho Kholid; Istiqomah Nur Rahmawati (Universitas Islam Negeri Palopo, 2026)
Despite the increasing prevalence of digital educational materials, code-switching as a viable teaching strategy has gained significant traction. This study aimed to identify structural codes of code-switching and their use in communication within the YouTube playlist